Management of anaphylaxis due to COVID‐19 vaccines in the elderly. Issue 10 (30th September 2021) - Bousquet, Jean; Agache, Ioana; Blain, Hubert; Jutel, Marek; Ventura, Maria Teresa; Worm, Margitta; Del Giacco, Stefano; Benetos, Athanasios; Bilo, Beatrice Maria; Czarlewski, Wienczyslawa; Abdul Latiff, Amir Hamzah; Al‐Ahmad, Mona; et al.
Abstract: Older adults, especially men and/or those with diabetes, hypertension, and/or obesity, are prone to severe COVID‐19. In some countries, older adults, particularly those residing in nursing homes, have been prioritized to receive COVID‐19 vaccines due to high risk of death. In very rare instances, the COVID‐19 vaccines can induce anaphylaxis, and the management of anaphylaxis in older people should be considered carefully. An ARIA‐EAACI‐EuGMS (Allergic Rhinitis and its Impact on Asthma, European Academy of Allergy and Clinical Immunology, and European Geriatric Medicine Society) Working Group has proposed some recommendations for older adults receiving the COVID‐19 vaccines. Anaphylaxis to COVID‐19 vaccines is extremely rare (from 1 per 100, 000 to 5 per million injections). Symptoms are similar in younger and older adults but they tend to be more severe in the older patients. Adrenaline is the mainstay treatment and should be readily available. A flowchart is proposed to manage anaphylaxis in the older patients.